2017
DOI: 10.1159/000453450
|View full text |Cite
|
Sign up to set email alerts
|

Should Age at Diagnosis Be Included as an Additional Variable in the Risk of Recurrence Classification System in Patients with Differentiated Thyroid Cancer

Abstract: Objective: To evaluate the influence of age at diagnosis on the frequency of structural incomplete response (SIR) according to the modified risk of recurrence (RR) staging system from the American Thyroid Association guidelines. Patients and Methods: We performed a retrospective analysis of 268 patients with differentiated thyroid cancer (DTC) followed up for at least 3 years after initial treatment (total thyroidectomy and remnant ablation). The median follow-up in the whole cohort was 74.3 months (range: 36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…We compared the clinic-pathologic features among these three groups of patients and found that elderly patients had higher proportion of male gender, advanced tumor grade, follicular subtype and advanced tumor stage (Summary Stage and AJCC 6 th Stage). These factors were all proved to be independent risk factors for prognosis in both univariate analysis and multivariable analysis which were consistent with previous reports 14 , 17 . Shah S et al found that there was a significantly larger percentage of excellent responders among young patients (age <55) than among old patients (age ≥ 55) 8 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We compared the clinic-pathologic features among these three groups of patients and found that elderly patients had higher proportion of male gender, advanced tumor grade, follicular subtype and advanced tumor stage (Summary Stage and AJCC 6 th Stage). These factors were all proved to be independent risk factors for prognosis in both univariate analysis and multivariable analysis which were consistent with previous reports 14 , 17 . Shah S et al found that there was a significantly larger percentage of excellent responders among young patients (age <55) than among old patients (age ≥ 55) 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Age at diagnosis has long been identified as an established prognostic factor for TC patients 8 , 17 . The cutoff value for age to predict prognosis has been controversial 9 - 14 . In our present study, we applied two most common used cut-off value: 45 years and 65 years old to divide patients into 3 groups: 20-44 years, 45-64 years, and ≥ 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have explored the age at diagnosis as a variable related to the RR in DTC patients. Our group analyzed the impact of age at the diagnosis of DTC on the frequency of structural incomplete response, considering the Modified Stratification System from ATA 2009 guidelines (Pitoia et al 2017). In this study, we did not find any age threshold that could distinguish an older group of patients with a higher risk for structural incomplete response neither at the initial response to treatment nor at the end of follow-up.…”
Section: Introductionmentioning
confidence: 84%
“…They suggested that incorporation of age in the ATA risk stratification would increase its power to predict response to therapy and mortality [ 49 ]. On the other hand, a few studies have not shown an important role for age in the estimation of risk of recurrence [ 50 ]. Pitoia et al retrospectively reviewed 268 patients with DTC (88.4% of them were ATA low- and intermediate-risk stages) with a median age at diagnosis of 45.9 years (range, 18-87 years) and found no impact of age on the probability of a structurally incomplete response at the initial evaluation and at last follow-up [ 50 ].…”
Section: Discussionmentioning
confidence: 99%